2015
DOI: 10.1124/dmd.114.062364
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Organic Anion Transporter 2 (SLC22A7): A Highly Efficient Transporter for Creatinine and Species-Dependent Renal Tubular Expression

Abstract: The contribution of organic anion transporter OAT2 (SLC22A7) to the renal tubular secretion of creatinine and its exact localization in the kidney are reportedly controversial. In the present investigation, the transport of creatinine was assessed in human embryonic kidney (HEK) cells that stably expressed human OAT2 (OAT2-HEK) and isolated human renal proximal tubule cells (HRPTCs). The tubular localization of OAT2 in human, monkey, and rat kidney was characterized. The overexpression of OAT2 significantly en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
101
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(105 citation statements)
references
References 43 publications
(61 reference statements)
4
101
0
Order By: Relevance
“…OAT2 is expressed in the basolateral membrane of renal proximal tubule cells as well as in the sinusoidal membrane of hepatocytes (Kobayashi et al, 2005;Cheng et al, 2012). One group showed that OAT2 was localized in both basolateral and apical membranes of human and cynomolgus monkey renal proximal tubules, but only in the apical membrane of rat proximal tubules (Shen et al, 2015). These findings suggest species differences for OAT2/Oat2 localization and possibly a role in reabsorption of OAT2 in primates.…”
Section: Transporters Involved In Creatinine Uptake In the Kidneymentioning
confidence: 69%
See 3 more Smart Citations
“…OAT2 is expressed in the basolateral membrane of renal proximal tubule cells as well as in the sinusoidal membrane of hepatocytes (Kobayashi et al, 2005;Cheng et al, 2012). One group showed that OAT2 was localized in both basolateral and apical membranes of human and cynomolgus monkey renal proximal tubules, but only in the apical membrane of rat proximal tubules (Shen et al, 2015). These findings suggest species differences for OAT2/Oat2 localization and possibly a role in reabsorption of OAT2 in primates.…”
Section: Transporters Involved In Creatinine Uptake In the Kidneymentioning
confidence: 69%
“…Creatinine showed a somewhat higher affinity toward OAT2 (K m = 986 mM) as compared with OCT2 and OCT3. Other groups also observed higher affinity transport of creatinine by OAT2 compared with that by other transporters (Shen et al, 2015). OAT2 might contribute to creatinine secretion, and possibly reabsorption in human renal proximal tubules, but clinical data are needed to support this hypothesis.…”
Section: Transporters Involved In Creatinine Uptake In the Kidneymentioning
confidence: 89%
See 2 more Smart Citations
“…Use of Monkey to Assess Transport by OCT2 and MATEs 245 at ASPET Journals on March 31, 2019 dmd.aspetjournals.org counterparts, likely function to mediated the secretion of substrates such as MFM, creatinine, and cisplatin (Urakami et al, 2004;Tanihara et al, 2007Tanihara et al, , 2009Imamura et al, 2011;Shen et al, 2015a). It is worth noting that although the impact of transporters on systemic exposure is relatively modest (less than threefold), their effects on drug distribution or tissue exposure could be more dramatic.…”
Section: Discussionmentioning
confidence: 99%